FRI0438 Treatment with Abatacept Prevents Experimental Dermal FIBrosis and Induces Regression of Established Fibrosis in a Preclinical Model of Systemic Sclerosis. (9th June 2015) - Ponsoye, M.; Frantz, C.; Ruzehaji, N.; Elhai, M.; Ruiz, B.; Cauvet, A.; Allanore, Y.; Avouac, J.
Abstract : Background: Early stages of systemic sclerosis (SSc) are characterized by inflammatory skin infiltrates mainly composed of activated T cells. Cytotoxic T-lymphocyte associated molecule-4 (CTLA-4) is a key regulator of T cell activation and preliminary data have suggested that it might contribute to SSc. Objectives: Our aim was to investigate the efficacy of the CTLA-4-Ig abatacept, an inhibitor of T cell activation, in reducing skin fibrosis in complementary mouse models of SSc. Methods: We first evaluated the antifibrotic properties of abatacept in the mouse model of bleomycin-induced dermal fibrosis, reflecting early and inflammatory stages of SSc. To assess whether abatacept might prevent the development of dermal fibrosis, six-week-old C57BL/6 mice received in parallel subcutaneous injections bleomycin (0.5 mg/ml) and intraperitoneal (i.p) injections of abatacept or purified human IgG1 at a dose of 100 mg every other day for three weeks. To assess whether abatacept might induce the regression of established dermal fibrosis, six-week-old C57BL/6 mice were challenged with bleomycin for 6 weeks and received i.p injections of 100 mg of abatacept or control IgG1 every other day during the last 3 weeks. Then, we investigated abatacept in the tight skin (Tsk-1) mice, an inflammation-independent mouse model of skin fibrosis. To this end, five-week-old Tsk-1 mice received i.p injections of 100 mg of abatacept or control IgG1 every other day for 5 weeks. Infiltrating leukocytes and T cells were quantified in lesional skin by immunohistochemistry. Results: Treatment with abatacept prevented the induction of bleomycin-induced dermal fibrosis: dermal thickness was significantly reduced by 48±5% in mice treated with abatacept compared to mice receiving the control IgG1 (p=0.03). Consistent with decreased dermal thickness, hydroxyproline content and myofibroblast counts were reduced upon treatment with abatacept by 63±4% (p=0.02) and 41±6% (p=0.04) respectively, compared to mice receiving the control antibody. In addition, treatment with abatacept led to decreased leukocyte and T cell infiltrates in the lesional skin of mice challenged with bleomycin. Abatacept also induced the regression of established bleomycin-induced dermal fibrosis: dermal thickness, hydroxyproline content and myofibroblast counts were reduced by 15±2% (p<0.01), 16±3% (p<0.01) and 33±5% (p=0.01) respectively, compared to mice receiving control antibody. Abatacept demonstrated no efficacy in Tsk-1 mice. Conclusions: Using complementary mouse models of SSc, we demonstrate that abatacept can prevent and induce the regression of inflammation-driven experimental dermal fibrosis. Translation to human disease is now required, and targeting early and inflammatory stages of SSc sounds the most appropriate. This strategy is currently under investigation in a phase-3 clinical trial assessing the efficacy of abatacept to improve skin involvement in patients with early diffuse SSc. Disclosure of Interest: None declared